The development of visualization of transmedia storytelling projects with a tree structure (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years, transmedia storytelling (TMS) technique is gatheringattention in Europe and America. Telling a story by using multiple kinds of media provides strong impression and immersivesensations with audiences. Therefore TMS technique has been incorporated in various fields.However, it is hard for creators to work on TMS project because of the complexity. The complexity is also an obstruction of popularization.In this study, by using the tree structure for TMS projects, we organize and visualize the complex content information of TMS. As a result, creators can work on a TMS project more efficiently. We analyze some successful TMS cases of different genres by applying them to a tree structure. Thereafter, we clarify what kind of effects creators can get by using a tree structure.